Peri-implant bone resorption risk of anterior maxilla narrow single implants: a finite-element analysis - Ivan Onone Gialain; Leonardo Folmer Rodrigues da Silva; Marlene Kasumi Gantier Takano; Rafael Yagüe Ballester; Marina Guimarães Roscoe; Josete Barbosa Cruz Meira (Medical Journals Sweden, 2022)
Statement of the problem: Narrow implants have been recommended in high esthetic demand regions to ensure greater buccal bone thickness (BBT) and minimize soft-tissue recession due to insufficient bone support. However, a limited area of bone-implant interface can increase the risk of peri-implant bone resorption due to occlusal forces.Purpose: This article encourages the use of evidence-based finite element analysis to optimize the aesthetic outcomes in maxillary lateral incisor single-supported implant crown by accurate biomechanical planning. This study aimed to analyze the best implant dimensions that would preserve the maximum BBT and avoid peri-implant bone resorption due to occlusal forces.Materials and methods: A maxilla segment was constructed based on anthropological measurements. Four implant diameters (Ø = 3.25; 3.50; 3.75 or 4.00 mm) and two lengths (L = 10 or 13 mm) were simulated. The occlusal force parameters were defined to simulate clinical conditions. The bone resorption risk analysis was based on Frost's mechanostat theory altering the strain output to strain energy density (SED). The peri-implant bone resorption risk indexes (PIBRri) were calculated by dividing the average of the top ten SED elements of the cortical and trabecular buccal wall by the pathologic resorption limit for each bone.Results: For trabecular bone, only the model Ø4.00L13 exhibited a low PIBRri. For cortical bone, all models presented a low PIBRri, except for models Ø3.25.Conclusion: The selection of a 3.25 mm dental implant to preserve a 2 mm BBT should be avoided since it generates a high peri-implant bone resorption risk induced by occlusal overload.